Percutaneous Vertebroplasty for Pregnancy-Associated Osteoporotic Vertebral Compression Fractures - Kim, Han Woong (The Korean Neurosurgical Society, 2010)
Osteoporosis is a worldwide problem and it mainly affects postmenopausal women. Osteoporosis associated with pregnancy or lactation is a rare condition. The incidence and mechanism of this phenomenon has not been clarified, but it can cause one or more vertebral compression fractures with severe, prolonged back pain in the affected women. We experienced this uncommon case, treated it with percutaneous vertebroplasty. A 35-old-woman visited our hospital with complaints of severe back pain and flank pain 2 months after normal vaginal delivery. She was diagnosed with osteoporotic vertebral compression fractures on the T5, 8, 9 and 11 vertebral bodies and we performed percutaneous vertebroplasty on the T8, 9 and 11 vertebrae with a good result. We present here an unusual case of pregnancy-associated compression fractures treated by percutaneous vertebroplasty.